(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Objective. To evaluate the impact of Fast-track (ERAS) protocols on functional recovery and quality-of-life outcomes in patients with tumors of the female reproductive system. Materials and methods. The study included 103 patients with ovarian, uterine body, and cervical tumors who underwent surgical treatment. The main group consisted of 49 patients managed according to ERAS protocols, while 54 patients receiving conventional perioperative care formed the control group. Functional status was assessed using the ECOG scale, and quality of life was evaluated with the EQ-5D index. Time to independent mobilization and recovery of self-care ability were also analyzed. Results. In the ERAS group, transition to ECOG 0–1 occurred after 3.9±1.0 days, and independent mobilization was achieved after 2.0±0.6 days. The EQ-5D index reached 0.82±0.05, which was significantly higher than in the control group (0.69±0.07). Functional recovery in patients receiving standard care was considerably slower. Conclusion. Fast-track protocols accelerate functional recovery and improve quality of life in gynecologic oncology patients. Implementation of ERAS pathways enhances the effectiveness of comprehensive treatment and promotes earlier social reintegration.